Prognostic Factors for Recovery of Vision in Canine Optic Neuritis of Unknown Etiology: 26 Dogs (2003–2018) - Posporis, Christoforos; Beltran, Elsa; Dunning, Mark; Espadas, Irene; Gillespie, Sabrina; Barry, Amy Teresa; Wessmann, Annette (Frontiers in Veterinary Science, 2019)
Optic neuritis (ON) is a recognized condition, yet factors influencing recovery of vision are currently unknown. The purpose of this study was to identify prognostic factors for recovery of vision in canine ON of unknown etiology. Clinical databases of three referral hospitals were searched for dogs with presumptive ON based on clinicopathologic, MRI/CT, and fundoscopic findings. Twenty-six dogs diagnosed with presumptive ON of unknown etiology, isolated (I-ON) and MUE-associated (MUE-ON), were included in the study. Their medical records were reviewed retrospectively, and the association of complete recovery of vision with signalment, clinicopathologic findings, and treatment was investigated. Datasets were tested for normality using the D'Agostino and Shapiro-Wilk tests. Individual datasets were compared using the Chi-squared test, Fisher's exact test, and the Mann-Whitney U-test. For multiple comparisons with parametric datasets, the one-way analysis of variance (ANOVA) was performed, and for non-parametric datasets, the Kruskal-Wallis test was performed to test for independence. For all data, averages are expressed as median with interquartile range and significance set at p<0.05. Twenty-six dogs met the inclusion criteria. Median follow-up was 230 days (range 21-1901 days, mean 496 days). Six dogs (23%) achieved complete recovery and 20 dogs (77%) incomplete or no recovery of vision. The presence of a reactive pupillary light reflex (p=0.013), the absence of fundoscopic lesions (p=0.0006), a younger age (p=0.038) and a lower cerebrospinal fluid (CSF) total nucleated cell count (TNCC) (p=0.022) were statistically associated with complete recovery of vision. Dogs with I-ON were significantly younger (p=0.046) and had lower CSF TNCC (p=0.030) compared to the MUE-ON group. This study identified prognostic factors that may influence complete recovery of vision in dogs with ON. A larger cohort of dogs is required to determine whether these findings are robust and whether additional parameters aid accurate prognosis for recovery of vision in canine ON.